2020
DOI: 10.1002/jbm.a.37066
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cells seeded decellularized scaffold promotes axonal regeneration in spinal cord injury rats

Abstract: Spinal cord decellularized (DC) scaffolds can promote axonal regeneration and restore hindlimb motor function of spinal cord defect rats. However, scarring caused by damage to the astrocytes at the margin of injury can hinder axon regeneration. Olfactory ensheathing cells (OECs) integrate and migrate with astrocytes at the site of spinal cord injury, providing a bridge for axons to penetrate the scars and grow into lesion cores. The purpose of this study was to evaluate whether DC scaffolds carrying OECs could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…2g), suggesting that shRNA-Mettl14 is helpful to stabilize microtubule structure and repair neurites. Axonal regeneration is beneficial to the recovery of motor function of hind limbs in rats with spinal cord defect, and the scar caused by astrocytes at the edge of injury will hinder axonal regeneration; NeuN, GFAP and NF-200 are used to evaluate neuronal, axonal regeneration and glial scab formation in the spinal cord [19,20]. Then, to determine whether shRNA-Mettl14 affects the repair of spinal cord defect, we detected the positive expression of GFAP, NeuN and NF-200 by immunohistochemistry.…”
Section: Shrna-mettl14 Reduced Sci and Promoted The Recovery Of Neurimentioning
confidence: 99%
“…2g), suggesting that shRNA-Mettl14 is helpful to stabilize microtubule structure and repair neurites. Axonal regeneration is beneficial to the recovery of motor function of hind limbs in rats with spinal cord defect, and the scar caused by astrocytes at the edge of injury will hinder axonal regeneration; NeuN, GFAP and NF-200 are used to evaluate neuronal, axonal regeneration and glial scab formation in the spinal cord [19,20]. Then, to determine whether shRNA-Mettl14 affects the repair of spinal cord defect, we detected the positive expression of GFAP, NeuN and NF-200 by immunohistochemistry.…”
Section: Shrna-mettl14 Reduced Sci and Promoted The Recovery Of Neurimentioning
confidence: 99%
“…3A ; all p < 0.001). NeuN, GFAP, and NF-200 represent neurons, axon regeneration, and glial scab formation in the spinal cord [ 21 , 22 ]. The number of NeuN was decreased significantly in SCI rats but increased in the EVs-treated rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[35] Olfactory ensheathing cells (OECs) also have the secretory function of BDNF, NGF, and GDNF. [36] Researchers have also found that mitochondria can be transferred from transplanted stem cells to host neuron cells as bioenergy supplements. [37] The transmission efficiency of mitochondria is also related to the regulation of inflammation and can be improved by regulating immune cells.…”
Section: Transplanted Cellsmentioning
confidence: 99%